Pluralism of legal understanding of postmodern society - Podkovenko , Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The research is aimed at analyzing the features of pluralism of legal understanding in postmodern society. The author asserts the importance and expediency in determining the features of the existing pluralism of the understanding of the law of the objective perception of legal reality with its complex globalization processes, which also leave their mark on the formation of legal doctrines, concepts, and theories. Pluralism in the system of values, including legal ones, makes it possible to understand that the greater the awareness of historicity and diversity, the more further interpretations, new conceptual structures, methods of evaluation, types of sensitivity and more internal dilemmas. Thus, the sense of responsibility for one’s own life and behavior becomes deeper. Experiencing values shows a person his individual moral task, awareness of internal duty and transferring it to the plane of practical interaction with other subjects. The most practical field that demonstrates such aspects is the field of law. The modern pluralistic approach to law makes it possible to identify and take into account qualitatively new facets of law, which are caused by the intensive development of social relations, changes in value orientations in the legal worldview, reorientation of legal practice to the principles of anthropocentrism, humanism, and justice. The pluralism of legal understanding once again emphasizes how much law is a multifaceted phenomenon. It expresses people’s desire for justice and freedom; public relations and social interest; volitional, formally defined and universally binding nature of legal norms; a certain value system is displayed. It is emphasized that pluralism in the understanding of law is a positive phenomenon that not only provides space for the development of theoretical legal thought, but also significantly enriches legal practice, providing space for freedom, critical thinking and objective assessment of state-legal phenomena. That is why the pluralistic worldview is an integral part of the legal thinking of the postmodern society, which is developing in the conditions of ideological, political and axiological diversity.